High-safety lithium manganese iron phosphate battery and preparation method thereof

Through magnesium ion doping and three-dimensional carbon materials covering lithium manganese iron phosphate materials, the problem of low conductivity and diffusion rate of lithium manganese iron phosphate batteries is solved, significantly improving the discharge capacity and rate performance of the battery, achieving high safety and Excellent cycle performance.

CN119230963APending Publication Date: 2024-12-31HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411592372.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The low electronic conductivity and low Li+ diffusion rate of lithium manganese iron phosphate batteries lead to poor discharge capacity and rate performance.

Method used

The magnesium ion doping and three-dimensional carbon material coated with lithium manganese iron phosphate material is formed to form a complex conductive network, increasing the diffusion path and electronic conductivity of Li+, and improving the diffusion rate of Li+.

Benefits of technology

The discharge capacity and rate performance of lithium manganese iron phosphate batteries are significantly improved, the circulation performance of the battery is enhanced, and high safety is maintained.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-safety lithium manganese iron phosphate battery and a preparation method thereof, and belongs to the technical field of lithium ion batteries. A preparation method of a high-safety lithium manganese iron phosphate battery comprises the following steps: S1, sintering a magnesium ion doped lithium manganese iron phosphate material and a three-dimensional carbon material, pyrolyzing the three-dimensional carbon material, depositing the pyrolyzed three-dimensional carbon material on the surface of the magnesium ion doped lithium manganese iron phosphate material to form a carbon layer, and cooling, crushing and grinding to obtain a magnesium ion doped lithium manganese iron phosphate material; the three-dimensional carbon layer coated magnesium ion doped lithium manganese iron phosphate positive electrode material is obtained; and S2, preparing a positive plate by taking the three-dimensional carbon layer coated magnesium ion doped lithium manganese iron phosphate positive electrode material as a raw material, and assembling the battery. By combining magnesium ion doping and three-dimensional carbon material coated lithium manganese iron phosphate material, the Li < + > diffusion rate and electronic conductivity of the lithium manganese iron phosphate material are improved, and the prepared battery not only has high safety, but also has high discharge capacity and excellent rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a high-safety lithium manganese iron phosphate battery and a preparation method thereof. Background Art

[0002] Lithium manganese iron phosphate is a product of lithium iron phosphate and lithium manganese phosphate. It has the same structure as lithium iron phosphate and an orderly olivine structure in terms of crystal form. Therefore, it has the same high structural stability as lithium iron phosphate. Manganese is cheaper than precious metals cobalt and nickel, and the cost of raw material preparation is low. In addition to the high safety performance and high thermal stability similar to lithium iron phosphate, it has the advantages of both lithium iron phosphate and lithium manganese phosphate, and can also make up for the shortcoming of low energy density of lithium iron phosphate.

[0003] There are two inherent defects in lithium manganese iron phosphate materials: one is that the strong PO bond restricts the free movement of electrons, resulting in low electronic conductivity; the other is that the olivine structure of lithium manganese iron phosphate materials causes its Li + The diffusion channel is one-dimensional, and its Li + The diffusion rate is low; these two defects result in low discharge capacity and poor rate performance of lithium manganese iron phosphate batteries.

[0004] Ion doping can cause Li, Mn or Fe defects in the lattice of lithium manganese iron phosphate materials, generate vacancies in the material lattice or change the interatomic bond length, which is convenient for Li + Movement in the lattice increases Li + The diffusion rate of lithium manganese iron phosphate can be increased, thereby improving the discharge capacity and rate performance of lithium manganese iron phosphate batteries; carbon coating modification can effectively enhance the conductivity of lithium manganese iron phosphate materials and thus improve their discharge capacity and rate performance, but the discharge capacity and rate performance of existing carbon-coated modified lithium manganese iron phosphate materials are still poor. Therefore, how to further improve the discharge capacity and rate performance of lithium manganese iron phosphate batteries is an urgent problem to be solved. Summary of the invention

[0005] The purpose of the present invention is to provide a high-safety lithium manganese iron phosphate battery and a preparation method thereof, so as to solve the low conductivity of lithium manganese iron phosphate materials and the + The problem of low diffusion rate is solved, thereby improving the discharge capacity and rate performance of lithium manganese iron phosphate batteries.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A method for preparing a high-safety lithium manganese iron phosphate battery comprises the following steps:

[0008] S1. Sintering the magnesium ion-doped lithium manganese iron phosphate material and the three-dimensional carbon material, and depositing carbon atoms or carbon molecules generated by the pyrolysis of the three-dimensional carbon material on the surface of the magnesium ion-doped lithium manganese iron phosphate material to form a carbon layer, and then cooling, crushing, and grinding to obtain a magnesium ion-doped lithium manganese iron phosphate positive electrode material coated with a three-dimensional carbon layer, recorded as LiMn 0.6 Fe 0.4-y Mg y PO4@C;

[0009] S2, LiMn 0.6 Fe 0.4-y Mg y PO4@C is used as raw material to prepare the positive electrode sheet and assemble it into a battery.

[0010] Furthermore, the sintering temperature in S1 is 100-120° C., and the sintering time is 10-12 hours.

[0011] Furthermore, the mass ratio of the three-dimensional carbon material and the magnesium ion-doped lithium manganese iron phosphate material in S1 is 1:25-35.

[0012] Furthermore, the magnesium ion-doped lithium manganese iron phosphate material described in S1 is prepared by the following steps:

[0013] Li2CO3, NH4H2PO4, MnC2O4, FeSO4 and MgO are mixed with deionized water to prepare a precursor slurry with a solid content of 40%; the precursor slurry is ground by a nano grinder for 4-6 hours and then spray-dried; the spray-dried precursor is calcined at 750°C for 8-10 hours in a nitrogen atmosphere, and cooled to room temperature to obtain a magnesium ion-doped lithium manganese iron phosphate material.

[0014] Furthermore, the molar ratio of Li2CO3, NH4H2PO4, MnC2O4, FeSO4 and MgO is n(Li2CO3):n(NH4H2PO4):n(MnC2O4):n(FeSO4+MgO)=0.5:1:0.6:0.4;

[0015] n(MgO):n(FeSO4)=0.005-0.015:0.385-0.395.

[0016] Furthermore, the three-dimensional carbon material described in S1 is prepared by the following steps:

[0017] The three-dimensional MOFs material and the organic carbon source are ultrasonically dispersed in an aqueous solution; the mixture is then reacted at 170°C for 10-12 hours, cooled, centrifuged, washed with deionized water and ethanol, and dried to obtain a precursor, and the precursor is pyrolyzed at 800-1000°C in a 5% H2 / Ar atmosphere at a rate of 1°C / min for 2 hours to obtain a three-dimensional carbon material.

[0018] Further, the three-dimensional MOFs material is one of ZIF-8, ZIF-67 and ZIF-4;

[0019] The organic carbon source is one of glucose, fructose and sucrose.

[0020] Furthermore, the mass ratio of the three-dimensional MOFs material to the organic carbon source is 0.1g:0.8-2.4g.

[0021] Furthermore, the positive electrode sheet in S2 is prepared by the following steps:

[0022] LiMn 0.6 Fe 0.4-y Mg y PO4@C was mixed with carbon black and PVDF in a mass ratio of 96:2:2 to prepare positive electrode slurry, and the slurry was made into positive electrode sheets through processes such as coating, rolling, slitting, and sheeting.

[0023] A high-safety lithium manganese iron phosphate battery, characterized in that it is prepared by the preparation method described in any one of claims 1 to 9.

[0024] Beneficial effects of the present invention:

[0025] (1) In the present invention, magnesium ions are doped into the lithium manganese iron phosphate material. When magnesium ions are doped, Mg will preferentially occupy the Fe position rather than the Li position, resulting in Li + The conductivity is higher; the doping of magnesium ions lengthens the Li-O bond length of the LiO6 octahedron in the olivine structure, thereby making Li + Easier to migrate, increase Li + The diffusion rate.

[0026] (2) The present invention prepares a three-dimensional carbon material coated with lithium manganese iron phosphate material. The three-dimensional carbon material can not only significantly improve the electronic conductivity of the material, but also form a complex conductive network that can be used for Li + Provide more diffusion paths, to some extent, Li + Bypassing the original one-dimensional diffusion channel, thereby increasing Li + The three-dimensional carbon material can also effectively stabilize the structure of lithium manganese iron phosphate materials and prevent the agglomeration of particles. This structural stability helps to maintain the Li + The diffusion channel is unblocked, thereby further improving the Li + Diffusion rate.

[0027] (3) The present invention combines magnesium ion doping and three-dimensional carbon material coating of lithium manganese iron phosphate material to improve the Li +The diffusion rate and electronic conductivity are improved, so that the prepared battery has not only high safety but also high discharge capacity and excellent rate performance. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] This embodiment provides a high-safety lithium manganese iron phosphate battery, which is prepared by the following steps:

[0031] (1) Preparation of magnesium ion doped lithium manganese iron phosphate material: Li2CO3, NH4H2PO4, MnC2O4, FeSO4 and MgO were mixed with deionized water at a molar ratio of 0.5:1:0.6:0.395:0.005 to prepare a precursor slurry with a solid content of 40%; the precursor slurry was grinded by a nano grinder for 6 hours and then spray-dried; the spray-dried precursor was calcined at 750° C. for 8 hours under a nitrogen atmosphere and cooled to room temperature to obtain a magnesium ion doped lithium manganese iron phosphate material;

[0032] (2) Preparation of three-dimensional carbon materials: 0.1 g ZIF-8 nanoparticles and 1.6 g glucose were ultrasonically dispersed in an aqueous solution; the mixture was then reacted at 170°C for 10 h, cooled, centrifuged, washed with deionized water and ethanol, and dried to obtain a precursor, which was then pyrolyzed at 1°C / min to 900°C for 2 h in a 5% H2 / Ar atmosphere to obtain a three-dimensional carbon material;

[0033] (3) The three-dimensional carbon material and the magnesium ion-doped lithium manganese iron phosphate material were mixed in a mass ratio of 1:35, sintered at 120° C. for 10 h, cooled, crushed, and ground to obtain the magnesium ion-doped lithium manganese iron phosphate positive electrode material LiMn coated with a three-dimensional carbon layer. 0.6 Fe 0.395 Mg 0.005 PO4@C;

[0034] (4) LiMn 0.6 Fe 0.395 Mg 0.005 PO4@C is made into positive electrode sheets and assembled into batteries: LiMn 0.6 Fe 0.395 Mg 0.005PO4@C is mixed with carbon black and PVDF in a mass ratio of 96:2:2 to form a positive electrode slurry. The slurry is made into a positive electrode sheet through processes such as coating, rolling, slitting, and sheet making. The positive electrode sheet, negative electrode sheet, separator and electrolyte are assembled into a battery.

[0035] Example 2

[0036] Compared with Example 1, this embodiment is different in that the step (1) of "mixing Li2CO3, NH4H2PO4, MnC2O4, FeSO4 and MgO with deionized water in a substance ratio of 0.5:1:0.6:0.395:0.005" is changed to "mixing Li2CO3, NH4H2PO4, MnC2O4, FeSO4 and MgO with deionized water in a substance ratio of 0.5:1:0.6:0.390:0.010"; the remaining raw materials and preparation process remain the same as those in Example 1.

[0037] Example 3

[0038] Compared with Example 1, this embodiment is different in that the step (1) of "mixing Li2CO3, NH4H2PO4, MnC2O4, FeSO4 and MgO with deionized water in a substance ratio of 0.5:1:0.6:0.395:0.005" is changed to "mixing Li2CO3, NH4H2PO4, MnC2O4, FeSO4 and MgO with deionized water in a substance ratio of 0.5:1:0.6:0.385:0.015"; the remaining raw materials and preparation process remain the same as those in Example 1.

[0039] Example 4

[0040] The present embodiment is different from the embodiment 2 in that the “three-dimensional carbon material and the magnesium ion-doped lithium manganese iron phosphate material are mixed in a mass ratio of 1:35” in step (3) is changed to “three-dimensional carbon material and the magnesium ion-doped lithium manganese iron phosphate material are mixed in a mass ratio of 1:30”; the remaining raw materials and preparation process remain the same as those in the embodiment 2.

[0041] Example 5

[0042] Compared with Example 2, the present embodiment is different in that the "three-dimensional carbon material and magnesium ion-doped lithium manganese iron phosphate material are mixed in a mass ratio of 1:35" in step (3) is changed to "three-dimensional carbon material and magnesium ion-doped lithium manganese iron phosphate material are mixed in a mass ratio of 1:25"; the remaining raw materials and preparation process remain the same as in Example 2.

[0043] Comparative Example 1

[0044] Compared with Example 1, the difference between this comparative example and Example 1 is that step (1) "preparing magnesium ion-doped lithium iron manganese phosphate material" is changed to "preparing lithium iron manganese phosphate material", and the preparation steps are: mixing Li2CO3, NH4H2PO4, MnC2O4, FeSO4 and MgO with deionized water in a molar ratio of 0.5:1:0.6:0.4 to prepare a precursor slurry with a solid content of 40%; grinding the precursor slurry with a nano grinder for 6 hours and then spray drying; calcining the spray-dried precursor at 750°C for 8 hours under a nitrogen atmosphere, and cooling to room temperature to obtain a lithium iron manganese phosphate material; the positive electrode material at this time is a lithium iron manganese phosphate material coated with a three-dimensional carbon layer; the remaining raw materials and preparation process remain the same as those in Example 1.

[0045] Comparative Example 2

[0046] Compared with Example 1, this comparative example differs in that ordinary carbon material is used, and carbon nanotubes are coated with magnesium ion-doped lithium iron manganese phosphate material; the positive electrode material at this time is carbon-coated magnesium ion-doped lithium iron manganese phosphate material; the other raw materials and preparation process remain the same as Example 1.

[0047] Comparative Example 3

[0048] Compared with Example 1, this comparative example differs in that ordinary carbon material is used, carbon nanotubes are coated with lithium manganese iron phosphate material, and the preparation method of the lithium manganese iron phosphate material is the same as that of Comparative Example 1; the positive electrode material at this time is carbon-coated lithium manganese iron phosphate material; the other raw materials and preparation process remain the same as those in Example 1.

[0049] The batteries prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were subjected to capacity tests, rate tests and cycle tests. The results are shown in Table 1:

[0050] Table 1

[0051] Discharge capacity (mAh / g) 0.2C 1C 2C 5C 10C After 300 cycles of 1C Example 1 150.1 146.1 134.3 123.5 115.0 132.9 Example 2 160.6 156.6 144.8 134.0 125.5 151.9 Example 3 155.3 151.3 139.5 128.7 120.2 143.7 Example 4 162.7 158.7 146.9 136.1 127.6 154.7 Example 5 164.6 160.6 148.8 138.0 129.5 157.4 Comparative Example 1 145.5 141.5 129.7 118.9 110.4 117.4 Comparative Example 2 146.2 142.2 130.4 119.6 111.1 118.7 Comparative Example 3 142.3 138.3 126.5 115.7 107.2 110.6

[0052] It can be seen from Table 1 that the batteries prepared in Examples 1 to 5 all have high discharge capacity and excellent rate performance and cycle performance; compared with Example 1, Example 2, and Example 3, it is found that increasing the amount of magnesium ion doping appropriately can improve the discharge capacity and rate performance of the battery, and can also enhance the cycle performance of the battery. The reason is that the doping of magnesium ions lengthens the Li-O bond length of the LiO6 octahedron in the olivine structure, thereby making Li + Easier to migrate, increased Li + However, excessive magnesium ion doping will cause the lattice distortion of lithium manganese iron phosphate, resulting in Li + The channel is blocked, which is not conducive to improving the discharge capacity, rate performance and cycle performance of the battery.

[0053] Compared with Example 2, Example 4, and Example 5, increasing the proportion of the three-dimensional carbon layer material in the positive electrode material is beneficial to improving the discharge capacity and rate performance of the battery and enhancing the cycle performance of the battery; the reason is that the three-dimensional carbon material can not only significantly improve the electronic conductivity of the material, but also form a complex conductive network that can be used for Li + Provide more diffusion paths, to some extent, Li + Bypassing the original one-dimensional diffusion channel, thereby increasing Li + The three-dimensional carbon material can also effectively stabilize the structure of lithium manganese iron phosphate materials and prevent the agglomeration of particles. This structural stability helps to maintain the Li + The diffusion channel is unblocked, thereby further improving the Li + Diffusion rate.

[0054] Compared with Example 1, Comparative Example 1 shows that without magnesium ion doping in the positive electrode material, the discharge capacity, rate performance and cycle performance of the battery will be reduced; Compared with Example 1, Comparative Example 2 shows that the battery discharge capacity, rate performance and cycle performance of the battery obtained by using ordinary carbon materials in the positive electrode material are lower than those using three-dimensional carbon materials; Compared with Example 1, Comparative Example 1 and Comparative Example 2, Comparative Example 3 shows that the battery discharge capacity is the lowest, and the rate performance and cycle performance are the worst without magnesium ion doping in the positive electrode material and using ordinary carbon materials.

[0055] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0056] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high-safety lithium manganese iron phosphate battery, characterized in that: The steps include: S1. Sintering the magnesium ion-doped lithium manganese iron phosphate material and the three-dimensional carbon material, pyrolyzing and depositing the three-dimensional carbon material on the surface of the magnesium ion-doped lithium manganese iron phosphate material to form a carbon layer, and then cooling, crushing and grinding to obtain a magnesium ion-doped lithium manganese iron phosphate positive electrode material coated with a three-dimensional carbon layer; S2. Using three-dimensional carbon layer-coated magnesium ion-doped lithium manganese iron phosphate positive electrode material as raw material to prepare positive electrode sheets and assemble them into batteries.

2. The method for preparing a high-safety lithium manganese iron phosphate battery according to claim 1, characterized in that: The sintering temperature in S1 is 100-120° C., and the sintering time is 10-12 hours.

3. The method for preparing a high-safety lithium manganese iron phosphate battery according to claim 1, characterized in that: The mass ratio of the three-dimensional carbon material and the magnesium ion-doped lithium manganese iron phosphate material in S1 is 1:25-35.

4. The method for preparing a high-safety lithium manganese iron phosphate battery according to claim 1, characterized in that: The magnesium ion-doped lithium manganese iron phosphate material in S1 is prepared by the following steps: Li2CO3, NH4H2PO4, MnC2O4, FeSO4 and MgO are mixed with deionized water to prepare a precursor slurry with a solid content of 40%; the precursor slurry is ground by a nano grinder for 4-6 hours and then spray-dried; the spray-dried precursor is calcined at 750°C for 8-10 hours in a nitrogen atmosphere, and cooled to room temperature to obtain a magnesium ion-doped lithium manganese iron phosphate material.

5. The method for preparing a high-safety lithium manganese iron phosphate battery according to claim 4, characterized in that: The molar ratio of the raw materials in S1 is n(Li2CO3):n(NH4H2PO4):n(MnC2O4):n(FeSO4+MgO)=0.5:1:0.6:0.4; n(MgO):n(FeSO4)=0.005-0.015:0.385-0.

395.

6. The method for preparing a high-safety lithium manganese iron phosphate battery according to claim 1, characterized in that: The three-dimensional carbon material described in S1 is prepared by the following steps: The three-dimensional MOFs material and the organic carbon source are ultrasonically dispersed in an aqueous solution; the mixture is then reacted at 170°C for 10-12 hours, cooled, centrifuged, washed with deionized water and ethanol, and dried to obtain a precursor, and the precursor is pyrolyzed at 800-1000°C in a 5% H2 / Ar atmosphere at a rate of 1°C / min for 2 hours to obtain a three-dimensional carbon material.

7. The method for preparing a high-safety lithium manganese iron phosphate battery according to claim 6, characterized in that: The three-dimensional MOFs material is one of ZIF-8, ZIF-67 and ZIF-4; The organic carbon source is one of glucose, fructose and sucrose.

8. The method for preparing a high-safety lithium manganese iron phosphate battery according to claim 6, characterized in that: The mass ratio of the three-dimensional MOFs material to the organic carbon source is 0.1g:0.8-2.4g.

9. The method for preparing a high-safety lithium manganese iron phosphate battery according to claim 1, characterized in that: The positive electrode sheet in S2 is prepared by the following steps: The magnesium ion-doped lithium manganese iron phosphate coated with a three-dimensional carbon layer was mixed with carbon black and PVDF in a mass ratio of 96:2:2 to prepare a positive electrode slurry, and the slurry was prepared into a positive electrode sheet through coating, rolling, slitting and sheeting.

10. A high-safety lithium manganese iron phosphate battery, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.